1997
DOI: 10.1111/j.1471-0528.1997.tb10648.x
|View full text |Cite
|
Sign up to set email alerts
|

Faecal incontinence after childbirth

Abstract: Objective To measure the prevalence and severity of postpartum faecal incontinence, especially new Design A cohort study with information on symptoms collected in home-based interviews and obstetric Setting Deliveries from a maternity hospital in Birmingham. Participants Nine hundred and six women interviewed a mean of 10 months after delivery. Main outcome measures New faecal incontinence starting after the birth, including frank incontinence, soiling and urgency.Results Thirty-six women (4%) developed new fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
188
5
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(210 citation statements)
references
References 17 publications
10
188
5
7
Order By: Relevance
“…The reported frequency of incontinence of stool in primiparous women ranges from 2 to 6% [MacArthur et al, 1997;Donnelly et al, 1998], and incontinence for either stool or £atus from 13 to 25% [Zetterstrom et al, 1999;Signorello et al, 2000]. After severe perineal laceration, the rate of anal incontinence rises to between 17 and 62% [Crawford et al, 1993;Sultan et al, 1993;Eason et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported frequency of incontinence of stool in primiparous women ranges from 2 to 6% [MacArthur et al, 1997;Donnelly et al, 1998], and incontinence for either stool or £atus from 13 to 25% [Zetterstrom et al, 1999;Signorello et al, 2000]. After severe perineal laceration, the rate of anal incontinence rises to between 17 and 62% [Crawford et al, 1993;Sultan et al, 1993;Eason et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that instrumental delivery is a risk factor for the occurrence of muscle defects in the internal and external anal sphincter (IAS resp. EAS), depending on the type of instrument usedöfor example, forceps or vacuum extraction [Sultan et al, 1993;MacArthur et al, 1997]öor interventions such as an episiotomy [Coats et al, 1980;Sultan et al, 1993]. It could be shown that postpartal fecal incontinence was signi¢-cantly more likely to be associated with instrumental delivery than with spontaneous vaginal delivery [MacArthur et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…2 The risk is higher, and incontinence is likely to persist in the long term after onset during pregnancy. 3,4 Evidence suggests that vaginal delivery can contribute to damage to the pelvic floor through muscle and fascial injury as well as disrupting the nerve supply.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported in up to 19% of women, and greatly affects quality of life 1,2 . While pudendal nerve injury during delivery is a well-recognized reason for sphincter dysfunction, the main source of incontinence is direct sphincter injury, specifically third-and fourth-degree intrapartum tears.…”
Section: Introductionmentioning
confidence: 99%